RESEARCH OF MEDICAL FACTORS AND REASONS FOR HEALING FAILURE OF PROBLEMATIC SKIN WOUNDS TREATED WITH PLATELET-RICH PLASMA - Tsvetan Sokolov; Aneliya Manukova (Peytchinski Publishing, 2020)
OBJECTIVE: To present our problematic skin wounds cases treated with PRP application of that has not responded to the treatment method. MATERIAL AND METHODS: Out of a total of 154 hospitalized patients with complex skin wounds 83 have been treated with platelet-rich plasma, comprising the Experimental group (EG), and 71 patients with comparable wounds have been treated by utilizing traditional techniques for the respective pathology, comprising the Control Group (CG). Ratings introduced by Cancela AM are used for the evaluation of the respective wound. Statistical analyzes have been performed by using the software SPSS (Statistical Package for the Social Sciences). All cases were treated in a procedure, which includes activated platelet-rich plasma. The treatment algorithm we used is as follows: first, there is surgical treatment and debridement of the wound. Activated plasma is used to infiltrate the wound edges and the fibrin clot is used to fill the wound itself. A sterile dressing soaked with physiological saline is applied. The treatment is repeated on a weekly basis until the wound problem is resolved in full. RESULTS: The results of our research indicate that 77 (92.78%) of patients enjoy a full recovery, while 6 (7.22%) of patients have no positive wound healing outcome (unhealed wound). CONCLUSION: Theoretical and clinical studies prove that the PRP method is a reliable, rational, and modern option for PSW treatment. It should not be seen as the only one and universal.